Cost-effectiveness of surgical treatments compared with early structured physiotherapy in secondary care for adults with primary frozen shoulder: an economic evaluation of the UK FROST trial. (2nd August 2021) - Corbacho, Belen; Brealey, Stephen; Keding, Ada; Richardson, Gerry; Torgerson, David; Hewitt, Catherine; McDaid, Catriona; Rangan, Amar; ,
Abstract : Aims: A pragmatic multicentre randomized controlled trial, UK FROzen Shoulder Trial (UK FROST), was conducted in the UK NHS comparing the cost-effectiveness of commonly used treatments for adults with primary frozen shoulder in secondary care. Methods: A cost utility analysis from the NHS perspective was performed. Differences between manipulation under anaesthesia (MUA), arthroscopic capsular release (ACR), and early structured physiotherapy plus steroid injection (ESP) in costs (2018 GBP price base) and quality adjusted life years (QALYs) at one year were used to estimate the cost-effectiveness of the treatments using regression methods. Results: ACR was £1, 734 more costly than ESP ((95% confidence intervals (CIs) £1, 529 to £1, 938)) and £1, 457 more costly than MUA (95% CI £1, 283 to £1, 632). MUA was £276 (95% CI £66 to £487) more expensive than ESP. Overall, ACR had worse QALYs compared with MUA (-0.0293; 95% CI -0.0616 to 0.0030) and MUA had better QALYs compared with ESP (0.0396; 95% CI -0.0008 to 0.0800). At a £20, 000 per QALY willingness-to-pay threshold, MUA had the highest probability of being cost-effective (0.8632) then ESP (0.1366) and ACR (0.0002). The results were robust to sensitivity analyses. Conclusion: While ESP was less costly, MUA was the most cost-effective option. ACR was not cost-effective. Cite this article: Bone Jt Open  2021;2(8):685–695.